OPTIMALISASI PENGELOLAAN PAJAK BAGI UMKM GARASI OTO CLINT - Amirul Ardiva, Amirul; Ramadhika CH, Bryan Sulthan; Jasmin, Fadli Aprian; Silmi, Silmi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
This activity aims to increase the understanding of MSMEs in Padang City regarding their tax calculations and obligations. Through intensive assistance, MSMEs are assisted in preparing financial reports and calculating appropriate taxes in accordance with applicable regulations. The results show a significant increase in tax understanding and awareness among MSMEs, which has the potential to increase tax compliance and local economic growth.